A Systematic Review with Meta-Analysis and Indirect Comparison of the Effectiveness of COVID-19 Anti-Interleukin Therapy - Yu. M. Gomon; A. S. Kolbin; A. M. Fahrutdinova; T. A. Usmanova; F. M. Sultanova; Yu. E. Balykina (Антибиотики и Химиотерапия, 2023)
Aim. Evaluation of the effectiveness of anti-interleukin drugs used in the pathogenetic therapy of COVID-19 in relation to the relative risks of 28-day mortality and the odds ratio of 14-day improvement of symptoms of the disease. Materials and methods. A systematic review of publications concerning the evaluation of the effectiveness of these drugs recommended for use as COVID-19 pathogenetic therapy, with meta-analysis and indirect comparison of the data obtained, was carried out. Results. The meta-analysis included 15 randomized and 8 non-randomized studies. In direct comparison of anti-interleukin drugs with controls, it was demonstrated that only tocilizumab and anakinra surpass standard therapy in terms of the relative risk of 28-day mortality (RR 0.85 [95% CI 0.74; 0.97] and 0.5 [95% CI 0.32; 0.80], respectively). Statistically reliable data were also obtained in favor of the effectiveness of levilimab in comparison with standard therapy according to the criterion of «improvement by the 14th day of the disease», which was 2.29 [1.31; 4.01]. With an indirect comparison of tocilizumab and anakinra, the latter showed greater effectiveness in reducing the 28-day mortality rate: the RR was 1.2 [95% CI 1.16; 1.25], P=0.0001. Conclusion. The meta-analysis of the results of the systematic review demonstrated the effectiveness of tocilizumab and anakinra in relation to the 28-day mortality rate, and levilimab in relation to the indicator «Improvement by the 14th day of the disease».